2020
DOI: 10.1111/jcmm.15616
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid protects dopamine neurons from rotenone‐induced neurotoxicity via activation of Nrf2 signalling

Abstract: Parkinson's disease (PD) is the second most prevalent central nervous system (CNS) degenerative disease. Oxidative stress is one of key contributors to PD. Nuclear factor erythroid‐2‐related factor 2 (Nrf2) is considered to be a master regulator of many genes involved in anti‐oxidant stress to attenuate cell death. Therefore, activation of Nrf2 signalling provides an effective avenue to treat PD. Ellagic acid (EA), a natural polyphenolic contained in fruits and nuts, possesses amounts of pharmacological activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
(74 reference statements)
4
14
0
Order By: Relevance
“…PJ administration restored the loss of DA level and its metabolite DOPAC, and slightly improved vertical activity. These findings corroborate previous results from Wei et al (2020), who showed that treatment with ellagic acid (EA) resulted in improvements in the motor performance of rotenone-treated rats [40]. EA…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…PJ administration restored the loss of DA level and its metabolite DOPAC, and slightly improved vertical activity. These findings corroborate previous results from Wei et al (2020), who showed that treatment with ellagic acid (EA) resulted in improvements in the motor performance of rotenone-treated rats [40]. EA…”
Section: Discussionsupporting
confidence: 92%
“…PJ administration restored the loss of DA level and its metabolite DOPAC, and slightly improved vertical activity. These findings corroborate previous results from Wei et al (2020), who showed that treatment with ellagic acid (EA) resulted in improvements in the motor performance of rotenone-treated rats [ 40 ]. EA also has been reported to protect against 6-hydroxydopamine (6-OHDA) and lipopolysaccharide-induced DA neuronal damage and related motor impairment [ 41 , 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the 6-OHDA model only can be used to test motor behavior. EA has also been shown to protect DA neurons from rotenone-induced neurotoxicity through activation of Nrf2 signaling [15]. It is important to note that, although rotenone been used to model PD, it is not specific for DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ellagic acid prevents rotenone-induced generation of S-nitrosylation of protein disulfide isomerase (SNO-PDI), a marker of Parkinson's disease in the cellular model [14]. EA has been shown to prevent dopamine neurons from rotenone-induced neurotoxicity through activating Nrf2 signaling cascade [15]. Rotenone inhibits the complex I of mitochondrial electron transport chain in a nonspecific manner and causes cellular demise [16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, some older studies have shown that EA can stimulate Nrf2 in other extra-testicular tissues. Indeed, EA protected from rotenone-induced astroglia cell damage, oxidant-induced endothelial dysfunction and atherosclerosis, methotrexate-induced, hepatocytes apoptosis via upregulation and activation of Nrf2 ( Ding et al, 2014 , Ebrahimi et al, 2019 , Wei et al, 2020 ). Besides, we have also shown that EA prevents DM-induced nephropathy by activation of Nrf2 (in press).…”
Section: Discussionmentioning
confidence: 99%